Estimation of Soluble Receptor Advanced Glycation End-Products in Diabetic Patients Type 2 Patients in Najaf City, Iraq - Nahlah F. Makki, Sanad B. Mahmmad, Ali A. Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Diabetes is a complex metabolic disruption affecting the glucose level of the human body. Intracellular hyperglycemia promotes mitochondrial reactive oxygen species (ROS) production, ROS directly improve the expression of inflammatory, these inflammations are associated with the level of soluble receptors for advanced glycation end-products (sRAGE) in serum. in this work assessed the level of (sRAGE) and study its potential as a biomarker for diabetes mellitus. The research included 108 Iraqis between the ages of (35-65) years of both sexes. The individuals were divided into two groups, (63) with type 2 diabetes mellitus (T2DM) and (45) control group, most of the tests serum have been measurements by colourimetric methods, and sRAGE levels in serum were evaluated by ELISA Technique. The results of the investigation showed that the sRAGE mean was more elevated compared to the mean of the control group (p < 0.00001). Statistical study of Pearson’s correlation illustrated that the sRAGE level is high positively with FBG, and HBA1C (r = 0.878, p < 0.00001), (r = 0.422, P=0.05) respectively. While, negatively correlation with insulin level (r = -0.204, p = 0.010). Furthermore, most the sRAGE level denoted a positive significant correlation with kidney function parameters inclusive urea, creatinine, and ACR, except eGFR was a negative significant (r = 0.422, p = 0.05), (r = 0.501, p = 0.01), (r = 0.435, p = 0.030), (r = -0.539, p = 0.011) respectively. These results support a strong relationship between serum sRAGE level and indicators of hyperglycemia, so we can conclude that it is a great biomarker for predicting of diabetes mellitus.